117k views
1 vote
Applying Properties of Exponents In Exercise,use the properties of exponents to simplify the expression.

(a) (e3)(e4)
(b) (e3)4
(c) (e3)-2
(d) e0

User Neoevoke
by
6.0k points

1 Answer

1 vote

Answer:

a)
e^(3)e^(4)=e^(7)

b)
(e^(3))^(4)=e^(12)

c)
(e^(3))^(-2)=e^(-6)

d)
e^(0)=1

Explanation:

a) Here we can use the product of powers rule:
x^(a)x^(b)=x^(a+b)


e^(3)e^(4)=e^(7)

b) In this ca we use power of a power rule:
(x^(a))^(b)=x^(a*b).


(e^(3))^(4)=e^(12)

c) We use the same rule above.


(e^(3))^(-2)=e^(-6)

d) Finally, we can use zero exponent rule:
x^(0)=1.


e^(0)=1

I hope it helps!

User DigiLive
by
5.7k points